PERENCANAAN MEDIA PEMBELAJARAN DI SMP IMTAQ DARURROHIM JAKARTA TIMUR - Santoso, Iman; Ulfah, Maria (Yayasan Panca Bakti Wiyata Pangandaran, 2024)
This article is motivated by the existence of the latest digital technology in everyday life, of course an educational institution must be able to adapt learning using digital technology. The aim of this research is to improve the quality of the learning process so that it can be more effective and achieve educational goals, and can also encourage students to be more active in utilizing learning media technology. The research conducted by researchers used qualitative methods. By collecting data through observations and interviews with a teaching staff at Imtaq Darurrohim Middle School, Cakung. Regarding the learning media planning implemented by teaching staff, it has gone well in terms of: Utilizing learning media. However, not all classes have a projector in each class, there are only a few available in the school, so it can hinder learning from taking place.